NEW RECORDS AND AN UPDATED LIST OF THE HERPETOFAUNA FROM NA HAU NATURE RESERVE, YEN BAI PROVINCE, VIETNAM - Sy Tuong, Dinh; Van Nghia, Ha; Huy Quang, Nguyen; Trung Duc, Ha; Van Phuong, Nguyen; Quang Vinh, Luu (Journal of Forestry Science and Technology, 2023)
Na Hau Nature Reserve (NR) was established in 2006, located in Van Yen district, Yen Bai province with a total area of 16,950 hectares. The nature reserve consists of a large area of natural montane forest with the habitat is evergreen broad-leaved forests and limestone forests with karst caves. The herpetofauna of this protected area is still poorly known, there is not much research about herpetofauna in this area, only one checklist in 2009 and one article in 2015. As a result of our field survey in Na Hau NR in September 2020, 13 species of amphibians and reptiles were recorded for the first time from Na Hau Nature Reserve, namely Takydromus sexlineatus, Sphenomorphus cryptotis, Tropidophorus hainanus, Oligodon cinereus tamdaoensis, Hebius boulengeri, Pareas hamptoni, Boulenophrys palpebralespinosa, Xenophrys maosonensis, Microhyla butleri, Amolops shihaitaoi, Odorrana nasica, Sylvirana maosonensis, Rana johnsi. In addition, we provide an updated list of 37 reptile species and 23 amphibian species from the study area. The nature reserve also harbors a high level of conservation concern with 17 threatened species, including 14 species listed in the IUCN Red List (2022), 13 species listed in the Vietnam Red Data Book (2007), and 10 species listed in the Governmental Decree No. 84 (2021).